Re-challenge of Platinum-based Chemotherapy for Platinum-refractory Patients with Recurrent or Metastatic Head and Neck Cancer: Claims Data Analysis in Japan - Makoto Tahara; Issei Doi; Tatsunori Murata; Sari Mishina; Shinji Takai; Hirokazu Kaneko (Journal of Health Economics and Outcomes Research)
**Background:** The role of platinum rechallenge in head and neck cancer (HNC) has not yet been fully evaluated.